1992
DOI: 10.1099/00221287-138-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Calcium regulation of growth and differentiation in Streptococcus pneumoniae

Abstract: Streptococcus pneumonk requires 0.15 mM-Ca2+ in the medium for optimal growth. Increasing the Ca2+ concentration to 1 mM triggers either a differentiathe state, competence for genetic transformation during exponential growth, or partial lysis as won as the cultures enter stationary phase. Genetic and physiological data both suggest that these responses are under the control of activator@), excreted in the presence of high Ca2+ concentrations. 45Ca2+ transport is also stimulated by the activator(s). The amilori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 45 publications
1
44
1
Order By: Relevance
“…4A, B). It has been extensively reported that the muramidase encoded by lytA represents the major autolytic function in S. pneumoniae under these experimental conditions (Lopez et al, 1997;Trombe et al, 1992). LuxSdependent autolysis was indeed suppressed by the lytA : : ery mutation, showing that LuxS activity prevents LytAdependent autolysis and contributes to cellular integrity during stasis (Fig.…”
Section: Impact Of Luxs On Vegetative Growthmentioning
confidence: 88%
See 4 more Smart Citations
“…4A, B). It has been extensively reported that the muramidase encoded by lytA represents the major autolytic function in S. pneumoniae under these experimental conditions (Lopez et al, 1997;Trombe et al, 1992). LuxSdependent autolysis was indeed suppressed by the lytA : : ery mutation, showing that LuxS activity prevents LytAdependent autolysis and contributes to cellular integrity during stasis (Fig.…”
Section: Impact Of Luxs On Vegetative Growthmentioning
confidence: 88%
“…Autolysis has classically been described in stationary-phase cultures, and depends on parameters such as the initial pH of the growth medium and its calcium concentration (Trombe et al 1992). It is related to competence development (Peterson et al, 2000;Trombe et al 1992). Recently, LytA-dependent autolysis of exponential cultures has been described in StkP-deficient mutant strains grown at alkaline pH (M.-C. Trombe & S. Romao, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations